Prêmio e castigo no Colégio Arquidiocesano de São Paulo (1908-1963) - Piñas, Raquel Quirino (2014)
This study aims to focus on the understanding of reward and punishment practices in the Archdiocesan School of São Paulo from 1908 to 1963. The intention of this research has been to understand the relation between rewards and punishments in the school as historically given teaching practices, educational actions that stimulate a type of training that is of particular interest of this school s culture, as well as its disciplinarian management. The hypothesis is that the meaning of the rewards and punishments are related, interdependent and promoted by the school s culture itself, in spite of the circulation of origin myths that aim to abolish the punishment within the Marist pedagogy . The time frame is established between 1908, year in which the Marist Brothers entered the institution, and 1963, when the study s main source, the journal Echo by Collegio Archidiocesano, stopped being published, highlighting the crisis in the boarding school system and a containment in the disclosure of the school s rewards. The study starts from the history of education and focus its analysis on the educational practices accessed through the documents that are part of the Memorial s collection of the Marist Archdiocesan School of São Paulo, and by the collation of data gathered from other schools archives. As a result, it was noticed that rewarding encouraged the competitiveness considered as a quality of masculine virtuosity of the political man to be formed